Social contributions in Romania - Attila Gyorgy (Romanian Journal of Fiscal Policy (RJFP), 2012)
Social contributions have an important impact on payroll policy. Also, social contributions represent a significant budgetary revenue item which can be viewed at the edge between taxation and insurance. Social contributions in Romania experienced many changes which ended in 2008. Nowadays, they are within a long transaction period towards partial externalization of the insurance activity to privately managed funds. The aim of this paper is to analyse the homogeneity of Romanian social security public scheme using annual data extracted from 2002-2009.The main findings reveal that social contributions reached the pinnacle of diversification, being too many, some of them with a small contribution rates; fiscal reforms which reduced contribution rates advantaged employers, and state will be interested to externalize this activity as far private sector will be able to assume this responsibility and the budgetary effects are acceptable for the public finance.
Keywords: E62; H24; 330; Social contributions; Fiscal policy; Herfindahl-Hirschman Index; Romania